(untitled) - Mader, Sylvia S. (New York, 2007)
Biology is a comprehensive introductory biology textbook for non-majors or mixed-majors courses that covers biology in a traditional order from the structure and function of the cell to the organization of the biosphere. The book, which centers on the evolution and diversity of organisms, is appropriate for a one- or two-semester course.. .
Keywords: Biology,Sinh vật học